Ekstraksi dan Karakterisasi Betasianin dari Kulit Buah Naga Merah (Hylocereus sp.) - Rendi Ananda; Minda Azhar (Jurnal Periodic Jurusan Kimia UNP, 2022)
Betacyanin is a water-soluble pigmentation compound  found  in the skin of red dragon fruit. Betacyanin extraction aims to determine the functional group and its maximum wavelength using FTIR and UV-Vis spectrophotometers, respectively. Extraction of betacyanin from dragon fruit peel using ethanol and water in a 1:1 ratio with a stirring speed of  900 rpm for 16 hours. Characterization of betacyanin using FTIR showed betacyanin has an amine group or bond (N-H) derived from betalamic acid which is typical at wave numbers 1798-1607 cm-1. At a wave number of 1486 cm-1 , it shows the presence of C=C strain vibrations from the aromatic ring. Betacyanin characterization using UV-Vis spectrophotometer showed a maximum wavelength of 530 nm.